COUNSELING TO INCREASE THE KNOWLEDGE OF PREGNANT WOMEN ABOUT EARLY DETECTION OF PREGNANCY DANGER SIGNS IN THE WORKING AREA OF THE DAMPIT HEALTH CENTER, MALANG REGENCY - Masyayih, Warda Anil; Siswati, Eny; Setyowati, Risha; Fatmawati, Istiadah (Journal of Indonesian Public Health Service, 2025)
Danger signs during pregnancy are critical conditions that may threaten the safety of both the mother and fetus if not detected early. This community service activity aimed to improve pregnant women’s knowledge regarding the early detection of pregnancy danger signs. The activity was conducted in May 2025 in the working area of the Dampit Public Health Center, Malang Regency, involving 25 pregnant women. Health education was delivered through interactive lectures, discussions, and question-and-answer sessions supported by visual media such as leaflets and PowerPoint presentations. Evaluation was conducted using direct questioning before and after the session to assess participants’ understanding. The results showed an improvement in participants’ knowledge of pregnancy danger signs, including the ability to identify key symptoms and recognize the importance of regular antenatal care. This activity demonstrates that health education is an effective strategy to enhance awareness and early detection of pregnancy complications.